2017
DOI: 10.1007/s11249-017-0947-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption Analysis of Hydrogen in Non-hydrogen-Charged Rolling Contact Fatigue-Tested 100Cr6 Steel

Abstract: Hydrogen diffusion during rolling contact fatigue (RCF) is considered a potential root cause or accelerator of white etching cracks (WECs) in wind turbine gearbox bearing steels. Hydrogen entry into the bearing steel during operation is thought to occur either through the contact surface itself or through cracks that breach the contact surface, in both cases by the decomposition of lubricant through catalytic reactions and/or tribochemical reactions of water. Thermal desorption analysis (TDA) using two experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
(95 reference statements)
0
19
0
Order By: Relevance
“…It is hypothesised that the occurrence of these features is a result of either, or a combination of; (1) an increase in traction between contacts at later stages of RCF operation, resulting in a rise of the maximum subsurface shear stress zone towards the surface. This would be significantly increased in the case of insufficient lubrication and higher surface roughness; (2) microindentations at the contact surface causing local regions of mixed/boundary lubrication regimes increasing the traction coefficient; (3) areas of localised increase in contact pressure, and (4) increase in the concentration of mobile diffusible hydrogen over longer RCF operation [44], where locally at the nearsurface, higher localised penetration and concentrations may exist and aid in the acceleration of these features. Figure 15 illustrates the hypothesised mechanisms for the formation of these features.…”
Section: Near-surface Weas/wecsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is hypothesised that the occurrence of these features is a result of either, or a combination of; (1) an increase in traction between contacts at later stages of RCF operation, resulting in a rise of the maximum subsurface shear stress zone towards the surface. This would be significantly increased in the case of insufficient lubrication and higher surface roughness; (2) microindentations at the contact surface causing local regions of mixed/boundary lubrication regimes increasing the traction coefficient; (3) areas of localised increase in contact pressure, and (4) increase in the concentration of mobile diffusible hydrogen over longer RCF operation [44], where locally at the nearsurface, higher localised penetration and concentrations may exist and aid in the acceleration of these features. Figure 15 illustrates the hypothesised mechanisms for the formation of these features.…”
Section: Near-surface Weas/wecsmentioning
confidence: 99%
“…Two factors to explain this could be: (1) steel cleanliness has shown that the raceway is 'cleaner' than the roller (see Sect. 2.3.1); (2) a lack of hydrogen being available to accelerate WEC formations [44]; and (3) the raceway is ~ 23% softer (590 HV) than the rollers (765 HV); therefore, the raceway is less prone to cracking due to an increased toughness. The importance of high toughness steel has been highlighted in the reduction in intergranular subsurface cracking and the subsequent movement of crack faces in generating WEA [41].…”
Section: Wec Initiation and Evolutionmentioning
confidence: 99%
See 3 more Smart Citations